Effects of silicon negative ion implantation in semi-insulating gallium arsenide. Issue 7 (3rd August 2019) - Yadav, Ajay; Dubey, S. K.; Bambole, V.; Dubey, R. L.; Sulania, I.; Kanjilal, D.
ABSTRACT: In the present work, effects of silicon negative ion implantation into semi-insulating gallium arsenide (GaAs) samples with fluences varying between 1 × 10 15 and 4 × 10 17  ions cm −2 at 100 keV have been described. Atomic force microscopic images obtained from samples implanted with fluence up to 1 × 10 17  ion cm −2 showed the formation of GaAs clusters on the surface of the sample. The shape, size and density of these clusters were found to depend on ion fluence. Whereas sample implanted at higher fluence of 4 × 10 17  ions cm −2 showed bump of arbitrary shapes due to cumulative effect of multiple silicon ion impact with GaAs on the same place. GXRD study revealed formation of silicon crystallites in the gallium arsenide sample after implantation. The silicon crystallite size estimated from the full width at half maxima of silicon (111) XRD peak using Debye-Scherrer formula was found to vary between 1.72 and 1.87 nm with respect to ion fluence. Hall measurement revealed the formation of n-type layer in gallium arsenide samples. The current–voltage measurement of the sample implanted with different fluences exhibited the diode like behavior.